The Role of Women in Family Economy in Kalipurwo Village: A Social and Islamic Economic Analysis - Imronah, 'Ainul; Nginayati, Eti (Jeksyah: Islamic Economics Journal, 2024)
This research was inspired by the shift of rice fields in Kalipurwo Village, Kuwarasan District, Kebumen Regency into kale farms, with many women working as kale farm laborers to support their families. The study aims to explore why women choose this work, their role in improving household income, and to assess Islamic economic justice for these workers. Using a descriptive qualitative approach, interviews were conducted with randomly selected informants. The findings reveal that women work as kale farm laborers due to necessity, fluctuating perceptions, lack of skills, and education. Their contribution is evident in household needs, such as supplementing their husband's income and covering daily expenses and school fees. The Islamic justice review highlights issues in licensing, wages, and spending. The study calls for government support to empower female workers and develop the farming sector.